DENTAL ARCH DIMENSIONS AND FORMS IN THE NIGER DELTA REGION OF NIGERIA - Okiemute, Etetafia Mabel; Anibor, Ese; Ijenwa, Benita Kelechi (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
This scrutiny assessed the dental arch dimensions and arch forms in a Niger Deltan population from Nigeria. The enquiry identified variations in tooth arch size. The inquiry compared the influence of gender on the dental parameters. This cross-sectional survey was done between February, 2021 and March, 2022. This study is a biometric analysis of dental casts of 206 subjects (104 males and 102 females) recruited from Teem Dental Clinic, Ekpan, Delta State, Nigeria. The dental arch sizes were determined. The proportions detailed are arch length, arch width, and arch form. The data were analyzed via the Statistical Package for the Social Sciences, version 22.0. Dental arch proportions (inter-canine width, inter-premolar width, inter-molar width and arch length) were lesser in females than in males. The Chucks arch form was considered in this scrutiny and the outcome was as follows: Tapered (49.5%), Ovoid (36.4%) and Square (14.1%). The dominant arch form was tapered, and the least common was square. Males mostly portrayed greater dental arch proportions than females.